An integrated approach towards future ballistic neck protection materials selection. (May 2013) - Breeze, John; Helliker, Mark; Carr, Debra J
Ballistic protection for the neck has historically taken the form of collars attached to the ballistic vest (removable or fixed), but other approaches, including the development of prototypes incorporating ballistic material into the collar of an under body armour shirt, are now being investigated. Current neck collars incorporate the same ballistic protective fabrics as the soft armour of the remaining vest, reflecting how ballistic protective performance alone has historically been perceived as the most important property for neck protection. However, the neck has fundamental differences from the thorax in terms of anatomical vulnerability, flexibility and equipment integration, necessitating a separate solution from the thorax in terms of optimal materials selection. An integrated approach towards the selection of the most appropriate combination of materials to be used for each of the two potential designs of future neck protection has been developed. This approach requires evaluation of the properties of each potential material in addition to ballistic performance alone, including flexibility, mass, wear resistance and thermal burden. The aim of this article is to provide readers with an overview of this integrated approach towards ballistic materials selection and an update of its current progress in the development of future ballistic neck protection.